PEMILU YANG BERINTEGRITAS DALAM NEGARA HUKUM DEMOKRATIS - Helen, Zennis (UNES Law Review, 2019)
The journal entitled Elections with Integrity in the State of Democratic Law was made for several reasons. First, elections are a means of implementing popular sovereignty as the implementation of normative provisions of the 1945 Constitution of the Republic of Indonesia, especially Article 1 Paragraph (2) which states that "Sovereignty be in the hands of the people and carried out according to the Constitution, ". Sovereignty in the hands of the people is also manifested through elections as a means of rotating leadership both at the national and regional levels carried out through direct, general, free and confidential principles. Secondly, elections in the 1945 Constitution are carried out by a general election commission which is referred to by the General Election Commission (KPU), Third, because the means of implementing people's sovereignty carried out by the KPU must be carried out by people who are not only professionals but also must have the main requirements, namely having dignity and integrity, Fourth, so that the implementation of the election is on track in accordance with the provisions of applicable legislation, supervision must be carried out by Law No. 7 of 2017 on Elections called the Election Supervisory Body (Bawaslu) ) The General Election Commission (KPU), Bawaslu, as the EMB has hierarchical levels from the central, provincial and district / city levels. This journal has two problem formulations, namely First, What is the urgency of the election as the implementer of popular sovereignty? Second, what is the election with that integrity?